Sweet Clara and the freedom quilt - Hopkinson, Deborah; Ransome, James (New York : Scholastic, 1993)
A young slave stitches a quilt with a map pattern which guides her to freedom in the north.
Keywords: Quilts -- Fiction; Slavery -- Fiction